PRECODER DESIGN BASED ON INTER-ANTENNA LEAKAGE MINIMIZATION FOR MU-MIMO - GEBREEL HAMED, ELSADIG SAEID (2012)
Multiple Input Multiple Output (MIMO) is an important technological development that makes use of the spatial dimension hitherto underutilized to increase the channel capacity. MIMO today is an integral part of many up to date wireless standards, such as: IEEE 802.lln for wireless LAN, WiMAX 2, and even the latest ITU-T mobile communication/ L TE-Advanced standard adopted by 3GPP in 20 II. The performance of the Multi-user MIMO (MU- MIMO) broadcast channel highly depends on the precoding scheme used for each user at the transmission front end. The MU-MIMO precoding design process is broadly classified in either of the following two frameworks, namely linear and nonlinear. Given the practical implementation challenges of the nonlinear precoding methods, preference is given to linear methods resulting in simple but high performance and efficient transmission methods. In this thesis, a new MU-MIMO precoding method is developed based on optimizing what is termed as Per-Antenna Signal to Leakage plus Noise Ratio (PASLNR). The optimization is facilitated using Fukunaga-Koontz Transform (FKT) that not only overcomes the problem of singularity but also helps reduce computation. Furthermore, we investigate the proposed method on a typical and practical wideband channel where OFDM is used to convert the wideband frequency selective channel into a set of narrow band flat sub-channels. The performance of the proposed method is validated against other methods available in the literature. finally, we extend the use of our proposed method to the extremely important and practical deployment scenario of cellular communication where MU-MIMO precoding is devised for the inter-cell interference cancelation by utilizing, what is known as, Multi-Cell Processing (MCP). We demonstrate the importance of precoding in cellular scenario by the capacity enhancement of both the cell edge users and the overall cellular system.